MEDIA PEMBELAJARAN SISTEM KENDALI PADA INSTALASI MOTOR LISTRIK BERBASIS PROGRAMMABLE LOGIC CONTROLLER DI SMK NEGMEDIA PEMBELAJARAN SISTEM KENDALI PADA INSTALASI MOTOR LISTRIK BERBASIS PROGRAMMABLE LOGIC CONTROLLER DI SMK NEGERI 1 DENPASARERI 1 DENPASAR - Ni Komang Ayu Sundari; Agus Adiarta; Wayan Mahardika Prasetya Wiratama (Universitas Pendidikan Ganesha, 2021)
This study aims to create learning media for control systems in electric motor installations based on Programmable Logic Controller (PLC) at SMK Negeri 1 Denpasar which is used to assist the learning process in the subject of Electric Motor Installation in class XII of Electrical Power Installation Engineering at SMK Negeri 1 Denpasar. This research is included in the type of research R & D (Research and Development). This study uses percentage statistical analysis techniques to process data from content experts, media experts, and trials for students. This study uses a questionnaire as an instrument of data collection for content experts, media experts, and students. The results of the research were: The results of the content expert test obtained a percentage of 95.45% with very proper qualifications, the results of the media expert test obtained a percentage of 95.23% with very proper qualifications. The range of scores for the 6 respondents in the small group test were all included in very high qualifications, and the range of scores for the 29 respondents in the large group test were all categorized as very high. The learning media for the control system in the Programmable Logic Controller-based electric motor installation at SMK Negeri 1 Denpasar is suitable for use in the learning process in class XII of the Electrical Power Utilization Installation Technique of SMK Negeri 1 Denpasar in the subject of Electric Motor Installation.